The Values of Inclusive Education in Islamic Religious Education: A Systematic Literature Review - Sarbini, Sarbini; Suhendi, Saca; Azzahra, Fitri Nurlatifah; Hoerotunnisa, Hoerotunnisa; Yuliawanti, Hani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This study aims to identify and analyze the values of inclusive education in Islamic Religious Education (IRE) through a Systematic Literature Review (SLR) guided by PRISMA 2020. A total of 22 articles published between 2020 and 2025 were reviewed to explore the integration of inclusive values—justice, equality, religious moderation, multiculturalism, and humanism—within the IRE curriculum and teaching practices. Data were collected from Google Scholar, DOAJ, Scopus, and Sinta using relevant keywords. Thematic synthesis using NVivo 12 Plus was employed to identify recurring patterns and research gaps. The findings reveal that inclusive education in IRE extends beyond accommodating students with special needs; it aims to cultivate universal human values rooted in the Islamic concept of rahmatan lil ‘alamin. IRE teachers play a central role in promoting inclusivity through humanistic and moderate pedagogies. The study highlights the urgency of developing an inclusive IRE curriculum model that balances cognitive, affective, and psychomotor domains while fostering tolerance, empathy, and respect for diversity. This research contributes theoretically to the discourse on inclusive Islamic education and practically to curriculum and teacher development.